Potential synergistic antihyperglycemic effects of co-supplemental Amla and Olive extracts in hyperlipidemic adults with prediabetes and type 2 diabetes: results from a real-life clinical study - Michel P., Hermans; Ahn, Sylvie A.; Rousseau, Michel F.; Seidel, Laurence; Albert, Adelin; Janssens, Isabelle; Dierckxsens, Yvan; Khan, Amjad (Frontiers in Nutrition, 2024)
Background: Hyperglycemia and type 2 diabetes mellitus (T2DM) poses a significant risk for cardiovascular diseases and associated complications in individuals with hyperlipidemia. Statin therapy, effective in reducing cholesterol and cardiovascular risks, paradoxically increases incident T2DM risk due to its adverse impact on insulin sensitivity. Therefore, there is a pressing need for safe, and effective adjunctive or alternative therapies to manage hyperglycemia in hyperlipidemic individuals. There is growing body of pharmacological evidence suggesting that Amla and Olive extract supplementation can be beneficial in managing hyperglycemia in individuals with hyperlipidemia. Objective: The present study aimed to assess for the first time the potential synergistic antihyperglycemic effects of a daily cosupplementation of 1000 mg Amla fruit and 50 mg Olive fruit standardized extracts (Cholesfytol NG ® ) over a 2-months period in hyperlipidemic adults with T2DM. Methods: This retrospective cross-sectional observational study analyzed treatment outcomes in 191 hyperlipidemic adults under the care of their physicians at 57 GP clinics in Belgium during routine clinical practice between March 19, 2020, and January 31, 2022. These participants received Cholesfytol NG ® as supplementary therapy to improve their metabolic health. The supplement was prescribed in an open-label, non-randomized manner, tailored to each participant's clinical status. Results: After 2-months of Cholesfytol NG ® supplementation, participants showed significant reductions in glycemia levels: in the T2DM group, levels decreased by 42.7 ± 17.9 mg/dL (27.9%, p < 0.0001), and in the prediabetic group, by 2.26 ± 11.5 mg/dL (4.7%, p = 0.0020). Conversely, no significant change was observed in participants with normal baseline glycemia (1.55 ± 10.3 mg/dL, p = 0.088). Overall, glycemia levels decreased from 96.4 ± 18.2 mg/dL to 94.0 ± 13.5 mg/dL (mean decrease of 2.4 ± 14.5 mg/dL, p < 0.0001). The supplement was well tolerated and no side-effects or serious adverse events, treatment-emergent effects were reported. The findings of this clinical study highlight the potential synergistic antihyperglycemic effects of co-supplementation with Amla and Olive fruit extracts in managing hyperglycemia, particularly in individuals with hyperlipidemia. These results suggest that this botanical combination may help mitigate risks associated with hyperglycemia and cardiovascular disease in hyperlipidemic population.